1997
DOI: 10.1046/j.1365-2265.1997.3361119.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin receptor imaging in somatotroph and non‐functioning pituitary adenomas: correlation with hormonal and visual responses to octreotide

Abstract: In the conditions of the study, in patients with acromegaly, positive somatostatin receptor scintigraphy predicts a hormonal response but the value of somatostatin receptor scintigraphy is limited by its low negative predictive value. In patients with non-functioning pituitary adenomas, negative somatostatin receptor scintigraphy predicts that there will be no visual improvement during octreotide treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 26 publications
1
30
1
4
Order By: Relevance
“…Therefore, it can be expected that most GH-secreting tumors can be visualized using 111 In-pentetreotide. Several studies in patients with acromegaly have shown a close association between the increased 111 In-pentetreotide uptake in the pituitary tumor and the inhibition of the pathologic GH secretion by octapeptide somatostatin analogs [15][16][17][18][19][20][21][22]. However, other studies could not reproduce these findings [23][24][25][26].…”
Section: Somatostatin Receptor Scintigraphymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it can be expected that most GH-secreting tumors can be visualized using 111 In-pentetreotide. Several studies in patients with acromegaly have shown a close association between the increased 111 In-pentetreotide uptake in the pituitary tumor and the inhibition of the pathologic GH secretion by octapeptide somatostatin analogs [15][16][17][18][19][20][21][22]. However, other studies could not reproduce these findings [23][24][25][26].…”
Section: Somatostatin Receptor Scintigraphymentioning
confidence: 99%
“…Various studies have demonstrated positive effects of this therapy on tumor size, visual field disturbances, or excessive secretion of tumor products in patients harboring these tumors [41][42][43]. Like in acromegaly, some studies in clinically non-functioning pituitary adenomas have shown a positive correlation between pituitary uptake of 111 In-pentetreotide and the inhibition of tumor growth, or excessive hormonal secretion (like FSH, LH or glycoprotein hormone subunits in some patients), or the improvement in visual field defects by octapeptide somatostatin analog therapy [15,22,41,44]. Generally, negative 111 In-pentetreotide scintigraphy predicted failure of somatostatin analogs to produce any kind of response in these studies [15].…”
Section: Somatostatin Receptor Scintigraphymentioning
confidence: 99%
See 1 more Smart Citation
“…A cintilografia com 111In-Pentreotide tem boa correlação com a resposta ao tratamento com octreotide (27,31,32), no entanto o seu alto custo limita o seu uso rotineiro.…”
Section: Teste Agudo Com Octreotide Subcutâneounclassified
“…Estas últimas têm sido relatadas em até 50% dos pacientes, mas freqüen-temente duram apenas l a 2 dias e podem não recidivar após as injeções subseqüentes (119,128). Em 101 pacientes tratados por até 30 meses, surgiram cálculos biliares em quatro pacientes e microlitíase em outros quatro (134).…”
Section: Octreotidaunclassified